Does Kinesiology Taping Enhance Athletic Performance? A Systematic Review of Sprint and Vertical Jump Outcomes - Hayuningrum, Cicilia Febriani; Putra, Kayika Andrewidjojo (Indonesian Journal of Physical Education and Sport Science, 2026)
Study purpose. Examine the effects of Kinesiology Taping (KT) on sports performance in order to evaluate its effectiveness for enhancing performance. However, its effectiveness remains controversial. This systematic review will attempt to clarify the available evidence on the effects of kinesiology taping (KT) on sprint and vertical jump performance in athletes. Materials and methods. In order to evaluate the effects of KT on sprint and jump performance in athletes, a systematic search for prospective as well as retrospective studies was conducted on PubMed and Google Scholar until March 2026. Google Scholar up to March 2026. all the studies which involved athletes, and measured their sprint performance or their vertical jump performance when they had tape on and when they did not have tape on. performance under taped and non-taped conditions. Quality of the included studies was assessed by PEDro scale and effect size was calculated by Cohen’s d. Results. Eight studies were investigated for the purpose of this review. Concerning the effect of KT on performance however, many studies have found no effect or mixed results and therefore its effectiveness is still debated. The aim of this review was to investigate the effects of KT on the sprint and vertical jump performance of athletes. meaningful improvement in performance. In contrast, moderate improvements Even for lower quality studies, there were moderate improvements in performance. However, the negative effects on the sprint performance of athletes after the application of KT were even greater in some cases. Some of the included studies reported slight negative effects of KT on sprint performance. Conclusions. No effect of KT on sprint and jump performance in athletes. sprint or vertical jump performance in athletes. This could be due to limitations and/or biases in the studies.